Atorvastatin and simvastatin as analgesic agents in experimental models - Dwajani, S. (Medknow Publications & Media Pvt Ltd, 2012)
OBJECTIVES: 1) To evaluate the analgesic effect of atorvastatin and simvastatin. 2) To compare analgesic activity of these with an established drug tramadol. MATERIALS AND METHODS: Healthy Albino rats were taken. They were randomly divided into 4 groups of six animals each. Group I: Normal Saline (0.5 ml), Group II: Tramadol (10 mg/kg BW), Group III: Atorvastatin (10 mg/kg BW) and Group IV: Simvastatin (10 mg/kg BW). The animals were subjected to 3 different tests at different interval of time. The tests conducted were tail clip method, Eddy′s hot plate and hot water tail immersion method. RESULTS: Atorvastatin and simvastatin differ significantly from control hence they have analgesic action and even at any of the time intervals they do not differ significantly from tramadol; hence their analgesic effect is nearly comparable to tramadol. The results of the present study indicate that atorvastatin and simvastatin have analgesic action. CONCLUSION: These statins are found to have analgesic effect other than hypolipidemic activity and can be used in these patients. However further study has to be undertaken in a broader way.